1986
DOI: 10.1177/019263658607049205
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Academic Performance of Athletes

Abstract: Student athletes have certain needs that differ from the general student population, says this writer, who proposes a com prehensive program to enhance their academic potential.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 1 publication
(1 reference statement)
0
5
0
Order By: Relevance
“…But, Bolig (1994) states that many sportsman students don't have a professional career in which the sport field they exercise and thus, they encounter stress related to their need of wondering about their career after school and their academic achievements. But Thompson (1986) states that student athletes' personal, academic and career needs differ from the general student population and points out that the athlete role is independently a source of career stress for the students. Figler and Figler (1984) mentioned career hardships of student athletes through a different point of view.…”
Section: Discussionmentioning
confidence: 99%
“…But, Bolig (1994) states that many sportsman students don't have a professional career in which the sport field they exercise and thus, they encounter stress related to their need of wondering about their career after school and their academic achievements. But Thompson (1986) states that student athletes' personal, academic and career needs differ from the general student population and points out that the athlete role is independently a source of career stress for the students. Figler and Figler (1984) mentioned career hardships of student athletes through a different point of view.…”
Section: Discussionmentioning
confidence: 99%
“…Athletics also develops students' sense of belonging or status within society and the educational environment (Goldberg & Chandler, 1992). It helps to develop personal and moral character while raising leadership, cooperation, coping strategies, risk taking, and achievement skills (Thompson, 1986). Dobosz & Beaty (1999) in their study indicated that athletes showed higher leadership ability than non -athletes.…”
mentioning
confidence: 98%
“…Athletics also contributed to students' sense of belonging or status within society and the school (Goldberg and Chandler, 1992). It developed personal and moral character while promoting leadership, cooperation, coping strategies, risk taking, and achievement behavior (Thompson, 1986). Students involved in athletics have considerably fewer discipline problems and school suspensions, and non-school related drug, alcohol, and tobacco abuse, and serious offenses with the law (Rombokas et al, 1995).…”
mentioning
confidence: 99%
“…Many supported a minimum grade, GPA, or behavior standards to allow students to participate at all levels of school sport (Ruffin, 1986;Thompson, 1986;McMillen, 1991;Morton et al, 1993;American Sports Institute, 1996).…”
mentioning
confidence: 99%
See 1 more Smart Citation